National estimates of kinship size and composition among adults with activity limitations in the United States - Adriana Reyes; Robert Schoeni; Vicki Freedman (Demographic Research, 2021)
Background: The number of adults living with limitations in daily activities in the United States is large, and projected to increase. Families, which are becoming more complex, are critical to the wellbeing of this population. Objective: We present national estimates of the size and composition of kin networks for adults with activity limitations. Methods: We use the 2013 Panel Study of Income Dynamics to assess kin relationships of adults aged 40 and older with an activity limitation. We assess kin relations up and down one generation and horizontally, including spouses, adult children, parents, siblings, step-kin, parent-in-laws, children-in-law, and sibling-in-laws. We estimate kinship size and differences across race/ethnicity, education, and marital status. We also estimate the number of helpers. Results: Adults with activity limitations have a substantial number of adult kin: 9.1 on average, while only 12Š have fewer than four kin. Spouses and adult biological children, the most common caregivers, account for less than one-third of these kin. Kin networks are much larger among those who report their background as Hispanic rather than non-Hispanic white or Black, married rather than unmarried, and less-than-college rather than college-educated. Conclusions: Despite concerns about increasing family complexity, we find that 88Š of individuals with a limitation have four or more family members, and as kin size increases the average number of kin helping increases from one to two. Contribution: We provide estimates of kinship size and composition for adults with disabilities, assessing the number of kin, types of kin, and sociodemographic differences.